anonymous
  • anonymous
16x – 3(4x + 7) = 6x –(2x + 21)what does x=?
Mathematics
katieb
  • katieb
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this
and thousands of other questions

bahrom7893
  • bahrom7893
multiply out the parenthesis: 16x - 12x - 21 = 6x - 2x - 21 Add 21 to both sides: 16x - 12x = 6x - 2x Move all x's to one side: 16x - 12x - 2x - 6x = 0 x = 0.. are u sure the question is right?
anonymous
  • anonymous
yes but it just doesnt make sense right!!!!!
bahrom7893
  • bahrom7893
yeah.. but that is the right answer, x = 0

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

bahrom7893
  • bahrom7893
Please click on become a fan if I helped, I really want to get to the next level!! Thanks =)
anonymous
  • anonymous
x=1
anonymous
  • anonymous
how
anonymous
  • anonymous
I'm wrong but it end up being 1=1
anonymous
  • anonymous
no oi just tried it and your right
anonymous
  • anonymous
4x=4x so that means 4/4 =x/x which means 1=1
anonymous
  • anonymous
or x=x
anonymous
  • anonymous
Solve the system of equations using elimination. x-3y=-4 and 2x+6y=5
anonymous
  • anonymous
Which means you can plug in any value for x and the equation holds true
anonymous
  • anonymous
and how did u get it
anonymous
  • anonymous
how did i get what?...
bahrom7893
  • bahrom7893
for the first equation there are infinite number of solutions.. it's not just 0 or 1
bahrom7893
  • bahrom7893
x-3y=-4 2x+6y=5 x = -4 + 3y 2(-4+3y)+6y = 5
anonymous
  • anonymous
yeah thats why i said you can plug in any value for x and the equation holds true
bahrom7893
  • bahrom7893
sorry didnt see that..
anonymous
  • anonymous
its all good
bahrom7893
  • bahrom7893
x = -4 + 3y 2(-4+3y)+6y = 5 x = -4 + 3y -8 + 6y + 6y = 5
bahrom7893
  • bahrom7893
x = -4 + 3y 12y = 13 x = -4+3y y = 13/12
bahrom7893
  • bahrom7893
x = -4+3y y = 13/12 x = -4 + 13/4 = -16/4 + 13/4 = -3/4 y = 13/12

Looking for something else?

Not the answer you are looking for? Search for more explanations.